The effects of TiO2 nanoparticles on the temperature-dependent electrical and dielectric properties of polypropylene - Zhang, Hao; Duan, Yubing; Xie, Maojie; Ma, Guoqing; Li, Pengfei; Qin, Jiafeng (Frontiers in Energy Research, 2022)
Nanoparticles are found to have the capacity to improve the specific properties of polypropylene (PP) for recyclable cable insulation material. However, previous studies have focused on the modification effect at room temperature, and few studies, on the nano-modification effect under high temperature environments. This article aims to study the effects of nanoparticles on the electrical and dielectric properties of PP at different high temperatures. Both TiO2 nanoparticles and PP/TiO2 nanocomposite samples are prepared in the laboratory by the wet chemical method and surface modification. Then, the AC and DC breakdown strength, conductivity, permittivity, and dielectric loss of the PP/TiO2 nanocomposite are measured at different temperatures. The results show that TiO2 nanoparticles introduce a small amount of charge traps into PP to restrain the conductivity and improve the breakdown strength of PP. But due to the additional interfacial polarization between TiO2 nanoparticles and the PP matrix, the permittivity and dielectric loss of the PP/TiO2 nanocomposite are enhanced, especially at low frequency.